There was a party for Langston - Reynolds, Jason (Atheneum Books for Young Readers, 2023)
A celebration of Langston Hughes and African American authors he inspired, told through the lens of the party held at the New York Public Library's Schomburg Center for Research in Black Culture in 1991.